EFFECT OF EXERCISE ON THE KINETICS OF ERYTHROCYTE SERIES AND SERUM LEVELS OF MUSCLE ENZYMES IN TWO-YEAR OLD THOROUGHBRED RACEHORSES - Collao C., José Luis (2013)
The effect of training in Thoroughbred horses on the kinetic of erythrocytic values (red blood cell count, hemoglobin and hematocrit) and serum muscle enzymes (CK, AST and LDH) was evaluated. Twenty four horses of 2 years of age (12 males and 12 females) were used among a group of horses that were selected to participate in race competitions. Blood samples were monthly taken before exercise (T0), and 5 minutes (T1), 1 hour (T2) and 24 hours (T3) after exercise during five months. The RBC count, hemoglobin concentration and hematocrit significantly increased in T1 (p<0.05) and in the fifth month (p<0.05). Also, LDH increased at T1 and T2 (p<0.05), while CK increases in T2 (p<0.05). AST did not show significant variation through collection times or months of training.